Iowa Birdline update, December 12, 1988 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1988)
Notes for the Iowa Birdline update for December 12, 1988. Highlights of the update include sightings of several species of Gulls, a brief appearance of a Brant, and a pair of Barrow's Goldeneyes. Also of note were sightings of Sandhill Cranes and a Red-bellied Woodpecker that was spotted at a feeder. Epson - sheet feed/flatbed